Additional left ventricular septal lead facilitates R-wave sensing of implantable cardioverter-defibrillator in arrhythmogenic right ventricular cardiomyopathy: a case report. Issue 1 (4th January 2023) - Lu, Wenzhao; Chen, Keping; Dai, Yan; Zhang, Shu
Abstract: Background: Implantable cardioverter-defibrillator (ICD) implantation is a key therapeutic option in arrhythmogenic right ventricular cardiomyopathy (ARVC) to prevent sudden cardiac death due to ventricular tachycardia (VT) and fibrillation (VF). However, sub-optimized R-wave sensing due to myocardium loss interferes with VT/VF identification and appropriate therapy. We tried to implant a 3830 lead to the left ventricular septum (LVS) to facilitate ICD sensing in an ARVC patient. Case summary: A 68-year-old woman diagnosed with ARVC was scheduled to undergo ICD implantation. Initially, no sites with suitable R-wave amplitudes were found in the right ventricle (RV) to deploy the defibrillation lead (<3.0 mV). It was likely due to severe RV involvement, but the LVS myocardium was more preserved based on cardiac magnetic resonance imaging. Therefore, we implanted a 3830 lead into the deep area of the septum to facilitate R-wave sensing. During the procedure from the right to left septum, the R-wave amplitude significantly increased (2.6 to 4.3–7.1 mV). Left ventricular septum pacing was finally achieved with favourable R-wave sensing (9.9 mV 24 h post-operation). The 3830 lead was plugged into the IS-1 port, while the defibrillation lead was plugged into the DF-1 port. After a 4-month follow-up, the R-wave amplitude of the 3830 lead was 11.1 mV. Discussion: When the R-wave sensing is not acceptable for ICD implantation in ARVC patients, it is critical to assess myocardial conditions comprehensively. If the septal myocardium is preserved, implanting a 3830 lead to the deep or LVS is feasible to improve R-wave sensing.